Tribute to Rt Hon Sir Ivor Richardson, PCNZM - McGrath, John (Victoria University of Wellington Law Review, 2015)
The following is a tribute to the late Sir Ivor Richardson. It was delivered by Justice John McGrath at a memorial service held at Old St Paul’s in Wellington on 29 January 2015.